2013
DOI: 10.2174/15680266113136660173
|View full text |Cite
|
Sign up to set email alerts
|

Therapy in Prion Diseases

Abstract: In the last two decades, knowledge of the neurobiology of prion diseases or transmissible spongiform encephalopathies (TSE) has significantly advanced, but a successful therapy to stop or delay the progression of these disorders remains one of the most challenging goals of biomedical research. Several obstacles to this achievement are in common with other neurodegenerative disorders: difficulties to move from experimental level to clinical stage; appropriate timing of intervention; correct set up of clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…In AD, soluble Aβ oligomers were initially considered the precursors of amyloid fibres and although their toxicity was demonstrated , only later were they considered central in AD pathogenesis . This concept has been extended to all the other protein‐misfolding disorders and we recently coined the term ‘oligomeropathies’ to highlight the role of soluble aggregates in the pathogenesis of neurodegenerative disorders .…”
Section: Prp106‐126 and The Role Of Oligomers In Pathogenesismentioning
confidence: 99%
“…In AD, soluble Aβ oligomers were initially considered the precursors of amyloid fibres and although their toxicity was demonstrated , only later were they considered central in AD pathogenesis . This concept has been extended to all the other protein‐misfolding disorders and we recently coined the term ‘oligomeropathies’ to highlight the role of soluble aggregates in the pathogenesis of neurodegenerative disorders .…”
Section: Prp106‐126 and The Role Of Oligomers In Pathogenesismentioning
confidence: 99%
“…30 Other phenotypes include a younger average age of onset, and gliosis of the thalamis. Epidemiological studies supported the possibility that the outbreak of BSE in cattle in the UK in the same period may have been 66 Atkinson et al…”
Section: Types Of Prion Diseasementioning
confidence: 99%
“…64 In experimental rodent models of prion disease, treatment with doxycycline at early stages (i.e., pre-clinical onset) showed good efficacy, while there was little or no apparent effect once clinical signs had emerged. 65 This suggests that treatment with doxycycline may be most useful as a preventive measure, for example for those patients who are carriers of the PRNP mutation that causes Familial Fatal Insomnia, 66 and this trial is currently underway. 67 A recent study has shown that treatment of prion disease in humans with non-human prion proteins may be a viable treatment option.…”
Section: 61mentioning
confidence: 99%
“…There are different methods of dealing with prion disease. 10,11 Given that total eradication of the diseases has not been possible, reducing their infectivity, reducing the substrate, and developing vaccinations have been explored.…”
Section: Introductionmentioning
confidence: 99%